Meaningful work and working conditions in the Third Sector. A critical approach for reflection through a theoretical review - Salguero González, Pedro (Cuadernos de Trabajo Social, 2025)
This article reviews theoretical perspectives on the relationship between meaningful work and the political dimension of labor, focusing on the Third Sector. Based on scholarly literature from the 1970s to 2024, when the Third Sector emerged as a distinct socioeconomic domain, it examines the tensions between workers' aspirations for meaningful employment and their actual working conditions. The analysis of critical theoretical perspectives suggests the development of a new labor subjectivity that appears to seek reconciliation between personal fulfillment and social commitment amid increasingly precarious conditions. The review makes three primary contributions: first, it synthesizes existing research on the connections between meaningful work and labor conditions within the Third Sector. Second, it proposes a theoretical framework to guide future empirical studies. Third, it advances ongoing debates regarding whether workplace precarity acts as a catalyst for alternative political organization or hinders social emancipation. The findings highlight the need for a renewed political analysis of meaningful work in the Third Sector and identify significant gaps in empirical research that warrant further investigation.
Keywords: meaningful work; third sector; vocation; politic; social change; precarity